2014
DOI: 10.1386/csmf.1.3.255_1
|View full text |Cite
|
Sign up to set email alerts
|

Men’s fit preferences in outdoor performance clothing: A qualitative investigation

Abstract: This article inductively examines men's fit preferences and practical fit issues in outdoor performance clothing to reveal how they are influenced by men's Body Mass Index (BMI) and height. Four focus group interviews (FGIs) were conducted with 21 men and the qualitative data was analysed using the grounded theory approach. Men's BMI influenced the following themes/sub-themes: fit (pant crotch, seat, hip fit; shirt proportion and fit; pant waist fit and pant leg fit) and sizing (inconsistency across brands; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Therefore, analyzing them is more complicated than that in a quantitative way. The other three remaining articles (Sohn et al, 2020;Rahman & Navarro, 2017;Stewart et al, 2014) applied mixed methods, a combination of quantitative and qualitative methods. Using a mixed method assists the researcher in achieving a better understanding of the issue and decreasing the research limitations (Creswell & Creswell, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, analyzing them is more complicated than that in a quantitative way. The other three remaining articles (Sohn et al, 2020;Rahman & Navarro, 2017;Stewart et al, 2014) applied mixed methods, a combination of quantitative and qualitative methods. Using a mixed method assists the researcher in achieving a better understanding of the issue and decreasing the research limitations (Creswell & Creswell, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In this period, only one study was published each year. This means that four articles (Sindicich & Black, 2011;Chattaraman et al, 2013;Stewart et al, 2014;Barry, 2015) were published in the third quarter of this twenty-one-year period, contributing to 40% of all articles. The constant trend tripled to three articles in 2016.…”
Section: Publication Date Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals may vary in their fit criteria, but the authors also found that men with higher BMIs prefer a looser fit for their jeans, dress shirts and polo shirts; as men's BMIs increased, they also preferred higher waistlines (Chattaraman et al , 2013). Later, Stewart et al (2014) used the developed scale by Chattaraman et al (2013) to examine men's fit preferences in outdoor performance clothing. In their study, overweight men tended to frequently mention about the fit of their pants in the crotch, seat and hip areas, as well as the fit and sizing inconsistencies of their shirts (Stewart et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Later, Stewart et al (2014) used the developed scale by Chattaraman et al (2013) to examine men's fit preferences in outdoor performance clothing. In their study, overweight men tended to frequently mention about the fit of their pants in the crotch, seat and hip areas, as well as the fit and sizing inconsistencies of their shirts (Stewart et al , 2014). Recently, Guo and Istook (2021) developed a 7-point scale of perceived fit preference from wearers (from −3: terrible to 3: excellent).…”
Section: Literature Reviewmentioning
confidence: 99%